"Be the Person You Ought to Be": A Convocation Speech to the Graduating Medical Students. (May 2021) - Fernandes, Ashley K.
In the age of coronavirus, our beloved Catholic Medical Association (CMA) medical students in the class of 2020, across the country, had "virtual graduations" and commencements, often separated from family and loved ones during a milestone in their vocations. Dr. Ashley K. Fernandes, MD, PhD, a CMA member since he was a medical student, and the 2015 Patrick Guinan CMA Mentor of the Year, was chosen by The Ohio State University College of Medicine as the 2020 Professor of the Year. According to The Ohio State University, "The Professor of the Year Award has been awarded each year since 1931 by the graduating class of The Ohio State University College of Medicine to a faculty member who has demonstrated excellence and commitment to teaching and in mentoring and serving as a role model to the class. This once-in-a-lifetime award is the highest honor that a faculty member can earn from the graduating class. The Professor of the Year is invited to address the class at the hooding ceremony." Dr. Fernandes delivered a "secularized version" of this address on April 30, 2020, "virtually, " and has modified his commencement address for our Catholic medical students as they begin their vocations in this most sacred vocation of healing. Summary: Dr. Ashley Fernandes addresses the newly graduating medical students of the Catholic Medical Association in a "virtual convocation speech" that implores them to remember the power and nature of medical profession itself; to be the person they ought to be through the exercise of the integrity and humility; and to remember whom they serve—God first, and then, the invaluable human person, made in His image.